Genetically modified cellular therapies for malignant gliomas - Kilian, Michael; Bunse, Theresa; Wick, Wolfgang; Platten, Michael; Bunse, Lukas (International journal of molecular sciences, 2021)
Despite extensive preclinical research on immunotherapeutic approaches, malignant glioma remains a devastating disease of the central nervous system for which standard of care treatment is still confined to resection and radiochemotherapy. For peripheral solid tumors, immune checkpoint inhibition has shown substantial clinical benefit, while promising preclinical results have yet failed to translate into clinical efficacy for brain tumor patients. With the advent of high-throughput sequencing technologies, tumor antigens and corresponding T cell receptors (TCR) and antibodies have been identified, leading to the development of chimeric antigen receptors (CAR), which are comprised of an extracellular antibody part and an intracellular T cell receptor signaling part, to genetically engineer T cells for antigen recognition. Due to efficacy in other tumor entities, a plethora of CARs has been designed and tested for glioma, with promising signs of biological activity. In this review, we describe glioma antigens that have been targeted using CAR T cells preclinically and clinically, review their drawbacks and benefits, and illustrate how the emerging field of transgenic TCR therapy can be used as a potent alternative for cell therapy of glioma overcoming antigenic limitations.